Changes in Level of C-reactive Protein at 0 hours and at 72 hours among Neonates with Suspected Sepsis at Neonatal Intensive Care Unit of Birat Medical College Teaching Hospital - Yadav, Ramesh; Rimal, Hemsagar (Birat Journal of Health Sciences, 2021)
Introduction: Neonatal sepsis still remains serious and potentially life-threatening events with a mortality rate of up to 50% in very premature infants. Efforts were made to improve laboratory sepsis diagnosis. C-reactive protein (CRP) is the most extensively studied acute phase reactant so far. Very few studies have been done to see the variation of serial measurement of CRP titer.Objectives: To find out the level of CRP titer at 0 hour and at 72 hours among neonates with suspected sepsis at the neonatal intensive care unit of Birat Medical College Teaching Hospital.Methodology:  It was a cross-sectional descriptive study from 26 March 2021 to 25 July 2021, to see serial CRP titre among the sepsis suspected neonates at the Neonatal intensive care unit of Birat Medical College Teaching Hospital. A Total of 95 cases of neonates suspected sepsis were enrolled and their serial CRP titre at o0 hour and 72 hours were studied.  The data was entered into Microsoft office excel and analyzed using statistical package for social sciences (SPSS 20.0)Results:  There was no significant association of gender, birth weight, mode of delivery and gestational age with an increase of CRP at 0 to 72 hours after birth. Among the enrolled neonates 34 had positive blood culture while 61 had blood culture which was sterile. It showed that, 70.6% who had blood culture positive had increased CRP level at 0 to 72 hours whereas only 29.4% had not no increment in CRP despite positive blood culture.Conclusions: CRP titre increment at 72 hours after the first one correlated better with culture proven sepsis in comparison to CRP titer increment at 0 hours after birth. The sensitivity, specificity, positive and negative predictive values as calculated in this study are not high enough to make it a good screening test. The test is not specific enough to rely upon as the sole indicator. The clinical judgment along with other hematological parameters and diagnostic markers along with serial CRP should be considered in evaluating a neonate for sepsis.